The role of job satisfaction as a mediating variable on leadership styles to employee performance - Siswanto Siswanto; Masyhuri Masyhuri; Ikhsan Maksum; Isnan Murdiansyah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This research aims to analyze the influence of transformational and transactional leadership styles mediated by job satisfaction on performance. The study used a quantitative approach to testing between variables; the sample used in this study was 60 respondents at PT. Cendana Teknika Utama resulted from the dissemination of questionnaires and interviews. The sampling technique used is saturated sampling. Analyze data using Smart-PLS. The results showed that transformational leadership harmed job satisfaction, transactional leadership had a positive effect on job satisfaction, and job satisfaction had no positive effect on performance. The results of the variable's influence on job satisfaction mediation on transformational and transactional leadership are different. Job satisfaction does not become a mediation variable for the influence of transformational leadership on performance. Nevertheless, job satisfaction becomes a mediation variable between transactional leadership influence and performance. The limitation of this study is that the number of respondents is too few. Several respondents in several companies expected to add to improve the generalization of the study results of the next study.